Mathematical applications : for management, life, and social sciences - Harshbarger, Ronald J.; James J. Reynolds (Lexington, Massachusetts : D.C. Health and Company, 1989)
This desirable goal is not always an easy one to realize with students whose primary interest is in an area other than mathematics. The purpose of this text, then, is to present mathematical skills and concepts and to apply them to areas that are important to students in the management, life, and social sciences.
Part One. Algebra review -- Part Two. Linear models -- Part Three. Nonlinear models -- Part Four. Probabilistic models -- Part Five. Calculus.
Includes index.
Keywords: MATHEMATICS